A refined chronology for the Middle and early Upper Paleolithic sequence of Riparo Mochi (Liguria, Italy). Issue 169 (August 2022) - Frouin, Marine; Douka, Katerina; Dave, Aditi Krishna; Schwenninger, Jean-Luc; Mercier, Norbert; Murray, Andrew S.; Santaniello, Fabio; Boschian, Giovanni; Grimaldi, Stefano; Higham, Thomas
Abstract: The Riparo Mochi rock shelter, located on the Ligurian coast of Italy, is one of the most important early Upper Paleolithic sites on the Mediterranean rim. Its ∼10-m-deep stratigraphy comprises a Mousterian sequence, followed by various development stages of the Upper Paleolithic. A series of radiometric dates on marine shells bearing traces of human modification has provided a chronological framework for the final Mousterian and the Proto-Aurignacian of the site. Based on modeling results, the end of the Mousterian was dated between 44.0 and 41.8 ka cal BP (68% probability) and the beginning of the Proto-Aurignacian between 42.7 and 41.6 ka cal BP (68% probability). However, these estimates were based on a limited number of radiocarbon ages in the Mousterian levels. Here, we report new dating of the Mochi sequence using luminescence techniques, along with new radiocarbon measurements. The combination of these results using a Bayesian modeling approach allows for the first time the establishment of a more precise timing for the Mousterian occupation at the site. We show that Mousterian groups were already present at Riparo Mochi by at least 65 ka and continued to occupy the site for another 20 ka. The transition to the earliest Upper Paleolithic at the site is centered around 44.3–41.1 ka (95.4% probability), providing our best age estimate for the beginning of the Early Upper Paleolithic and the establishment of modern human groups in the Balzi Rossi. The sequence continues upward with a more evolved Aurignacian phase and a Gravettian phase starting at ∼26 ka or earlier.